LOVE AND BELONGING NEEDS IN ISTIQOMAH’S NOVEL SERIBU MUSIM MERINDUIMU - Nurhasanah Nurhasanah; Purwanto Siwi; Muhammad Ali Pawiro (Universitas Islam Sumatera Utara, 2023)
The aim of the study is to explore the protagonist's effort in fulfilling her love and belonging needs as viewed from Abraham Maslow's theory. There are four different levels of Maslow’s hierarchy of needs discussed: security and safety needs, social needs, and esteem needs. Maslow's hierarchy of needs is often displayed as a pyramid. The lowest levels of the pyramid of needs are made up of the most basic needs, while the most complex needs are at the top. Once lower-level needs have been met, people can move on to the next level of needs. The researchers identify the characteristics of Reysa as the protagonist in Seribu Musim Merinduimu and analyze her fulfillment of love and belonging needs. This novel was chosen because nowadays people think that love is the right of everyone, regardless of their marital status. The researchers use qualitative descriptive analysis to reveal the findings, as the focus of the research revolves around people and their surroundings. The data were collected from the novel and other relevant sources. From the analysis of the novel, the researchers find the four hierarchy of needs. In the context of the hierarchy of needs, she faces obstacles in fulfilling her love and belonging needs because she loves a married man. But in the end, she is able to fulfill her needs for love and belonging after going through various challenges.